PERANCANGAN SISTEM PENYIRAMAN TANAMAN OTOMATIS MEGGUNAKAN ARDUINO - Nofri Wandi Al Hafiz; Erlinda Erlinda (Universitas Islam Kuantan Singingi, 2020)
Every plant really needs water to be able to live and as much as possible to be watered on time, because if it is too late, the growth of the plant will be hampered or even unable to develop and die, therefore there are other alternatives for plant lovers in doing plant care and not making it. We are busy in watering plants, namely using plant watering technology using Arduino electronic control, where this tool can distribute water to each plant by detecting water needs in the plant, if the planting medium on the plant is dry, it will turn on the tool and water the plant. The current method of watering plants requires energy and takes time for us to water the plants and we don't even know whether these plants need water because the surface of the soil is dry, so there is still a lot of water available inside, with this controller the water content can be determined, if the water content in the low soil, the tool will automatically turn on and water the plants